Experimental Characterisation of Photovoltaic Modules with Cells Connected in Different Configurations to Address Nonuniform Illumination Effect. (1st April 2019) - Paul, Damasen Ikwaba
Abstract : Most concentrating systems that are being used for photovoltaic (PV) applications do not illuminate the PV module uniformly which results in power output reduction. This study investigated the electrical performance of three PV modules with cells connected in different configurations to address nonuniform illumination effect. PV module 1 is the standard module consisting of 11 solar cells connected in series whereas PV module 2 is a proposed design with 11 cells in three groups and each group consists of different cells in series connections. PV module 3 is also a new design with 11 cells in two groups and each group consists of different cells connected in series. The new PV modules were designed in such a way that the effect of nonuniform illumination should affect a group of cells but not the entire PV module, leading to high power output. The PV modules were tested under three different intensities: uniform, low nonuniform, and high nonuniform illumination. When the PV modules were tested at uniform illumination, the total maximum power output of PV module 1 was higher than that of PV module 2 and PV module 3 by about 7%. However, when the PV modules were tested at low nonuniform illumination, the total maximum power output of PV module 2 was higher than that of PV module 1 and PV module 3 by about 4% and 7%, respectively. This difference increased to about 12% for PV module 3 and 17% for PV module 1 when the modules were tested at high nonuniform illumination. Therefore, the best PV module design in addressing nonuniform illumination effect in solar collectors is PV module 2. In practical situation this implies that manufacturers of PV modules should consider designing modules with groups of cells in series connection instead of all cells being connected in series.